ANALISIS RISIKO NATION BRANDING DALAM PENYELENGGARAAN KAWASAN EKONOMI KHUSUS MANDALIKA - Sonny T Danaparamita (Jurnal Geuthèë: Penelitian Multidisiplin, 2021)
his research is a normative juridical research that analyzes the risk of branding in the administration of economic zones. Especially in the mandalika area, in this study the theory used is the pure legal theory of Hans Kelsen which has two functions, namely: first, on the one hand it functions as an epistemology and methodology which legal scholars use as the basis for legal science (rechtsdogmatic); and secondly, it also functions critically with the opposite position to conventional legal science. The theory is to answer research problems, namely First, related to the risk of Nation Branding in the Special Economic Zone and Second, the reality of social justice in the Special Economic Zone by taking the research locus in the Special Economic Zone of Mandalika. The findings in this study include that in general investment law as a nation branding framework in the administration of special economic zones in Mandalika, is characterized by inconsistencies in the application of law, which tends to eliminate the collective sense of justice of the Indonesian people.